Analysis of the Use of Health Education Methods in Increasing Public Nutrition Awareness - Amina Intes; Benny Novico Zani; Surya Syarifuddin; Irine Christiany; Sulistyo Andarmoyo (Yayasan Adra Karima Hubbi, 2024)
Public nutritional awareness is an important factor in realizing a healthy diet and balanced lifestyle. Health education methods have a vital role in increasing understanding and awareness of nutrition among the public. This research aims to analyze the effectiveness of health education methods in increasing public nutritional awareness. The method in this research uses a quantitative approach with a survey method involving various groups of people with social and educational backgrounds. The educational methods used consist of several methods with educational material about nutrition. Data was collected through questionnaires before and after the educational intervention was carried out. The results of this research show an increase in the level of public nutritional awareness after implementing health education methods. Respondents who took part in the education program showed better knowledge about nutritional value, healthy eating patterns, and their impact on health. Apart from that, participants also showed more positive behaviour regarding food choices and a healthy lifestyle. The conclusion of this research is that the health education method has proven to be effective in increasing public nutritional awareness. Implementing educational programs can influence people's knowledge, attitudes and behaviour regarding nutrition and health. This provides a strong basis for continuing to develop and improve health education efforts to create a society that is more aware of the importance of nutrition in maintaining health and well-being.